Penggunaan Kuaci pada Pembelajaran Volume Bola di Kelas - Widiawati Widiawati; Helni Indrayati; Herdiyan Siswanto (Jurnal Pendidikan Matematika:Judika Education, 2019)
The purpose of this study was to determine the trajectory of student learning on ball volume using quaci in Class IX. The research method, using a Validation Study design involving 38 students of class IX SMP Pagaralam PGRI. The stages of design research in learning consist of three phases: preparation for the experiment, design experiment, and retrospective analysis. Learning is carried out through three activities consisting of observing sunflowers, taking sunflower seeds, and wrapping them in accordance with PMRI's approach to ball volume material. The results showed that students could understand the concept of ball volume by completing a series of these activities. In addition, students have their own strategies in solving problems in each activity to express it in abstract form. Conclusion, the use of quaci in learning volumes of ball gives positive results for students in understanding problems related to real life in accordance with the PMRI approach. Keywords: Design Research, Kuaci, PMRI